Comparative Study of Single-glazed and Double-glazed Windows in Terms of Energy Efficiency and Economic Expenses - Forughian, Samaneh; Taheri Shahr Aiini, Masoud (Journal of History Culture and Art Research, 2017)
Saving fossil fuels and the use of clean sources of energy lead to reduce in building operating costs, protect the environment and people’s health. Windows are the most vulnerable part of building where energy loss occurs. Double-glazed windows are very effective in keeping inside temperature isolated from outside; thereby, saving electrical and thermal energy. The current study estimates the numerical changes in cooling and heating load in case of replacement double-glazed window with single-glazed window and calculates saving level for this replacement. In this context, this paper presents a model of real samples taken in Mashhad climate. To ensure the accuracy of the simulation results, real results were compared with electricity and gas bills. To calculate energy related parameters such as cooling load, heating load, the consumption of gas and electricity, the energy simulation software (Design Builder) was used. The research method was a quantitative analysis based on energy consumption modeling, associated with building windows which comes in four sections. The field study was also used to compare with real electricity and gas bills. As the first stage, samples of the plan were identified, based on the observation of climate models and library studies. Then, simulation parameters such as window materials and internal and external walls were considered. The simulation was performed based software’s parameters and model limitations were determined based on thermal, lighting, climatic and architectural parameters. Finally, the experimental and practical data were used to determine the validity of the model under Mashhad climate conditions. Overall, the results indicated that double-glazed windows could save 50% of entire building loads, 0.2% on power consumption, 16.2% on gas and 12.4% on overall households’ energy consumption.